The Effect of Liquidity, Leverage, and Profitability on Company Value with Intellectual Capital Moderation at BEI Banks - Nurfatiha Pasya Salsabilla; Elfiswandi Elfiswandi; Lusiana Lusiana (International Journal of Economics and Management Research, 2025)
This study aims to analyze the effect of liquidity, leverage, and profitability on company value with intellectual capital as a moderating variable in banking companies listed on the Indonesia Stock Exchange for the period 2020–2024. In this study, the author conducted a study on the Intellectual Capital Model as a Moderating Variable Reviewed from Liquidity, Leverage, and Profitability Its Influence on Company Value in Public Banking Sector Companies Listed on the Indonesia Stock Exchange in 2020–2024. The object of this study is banking listed on the Indonesia Stock Exchange in 2020–2024. Researchers conducted this research on the Indonesia Stock Exchange (IDX) or Indonesian Stock Exchange (IDX) site www.idx.co.id, https://finance.yahoo.com and as a complement to researchers in seeking information through the internet, print media, and other media. The population in this study was 44 Companies. Population refers to the entire data that has a wide scope and large number in a study. Based on the previous definition, the population in this study is the Public Banking Sector Companies Listed on the IDX in 2020-2024. This sample selection method uses a purposive sampling method, namely sample selection based on certain criteria and systematics. The results of the study indicate that the results of the discussion of data analysis through proof of the hypothesis of the issues that can be raised regarding company value (Liquidity, Leverage, and Profitability) are moderated by intellectual capital in Banking Sector Companies Listed on the Indonesia Stock Exchange in 2020-2024, namely Liquidity has a significant effect on company value in Banking Sector Companies Listed on the Indonesia Stock Exchange in 2020-2024. While Leverage does not have a significant effect on company value in Banking Sector Companies Listed on the Indonesia Stock Exchange in 2020-2024.